PELANGGARAN TERHADAP PRINSIP-PRINSIP BADAN HUKUM DI PT. SARI AMERTA UTAMA DENPASAR SUATU KAJIAN BERDASARKAN UNDANG-UNDANG NO. 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Mandraguna, Griyo; Westra, I Ketut; Sri Indrawati, Anak Agung (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 04, Juni 2013, 2013)
Violation of the principle of legal entities in accordance with Act No. 40 of2007 Issues arising from violations of the principle of legal entity using otherresearch methods juridical emperis in the company of Sari Amerta UtamaDenpasar . Legal entities violated the principle of individual responsibility for anyloss liability that applies both to shareholder, directors or the board ofcommissioners, and can also be renteng liable in case of loss due to breach thecompany, carried out by more and one member of the board of directors, boardmember or shareholder.
Keywords: Violation of Principles, legal entity